Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/ageing/32.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Medical conditions as risk factors for pressure ulcers in an outpatient setting

Abstract: it is important that physicians recognise that patients with many medical conditions may be at higher risk for pressure ulcers so that even in the ambulatory care environment appropriate prevention and detection strategies can be directed towards the patients who are most likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 27 publications
4
77
2
3
Order By: Relevance
“…1 The number of individuals who needed long-term care at Japanese home under Japan-specific long-term care insurance system was determined to be 5.8 million in 2015; this was approximately three times higher than it was when the system was implemented in 2000. 2,3 Most of the individuals have specific medical conditions that are associated with pressure injury development; 4 consequently, the number of individuals at risk of developing pressure injuries at home in Japan appears to be increasing. Reportedly, this incidence rate was 13%, 5 which was higher than that in patients admitted to university and general hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…1 The number of individuals who needed long-term care at Japanese home under Japan-specific long-term care insurance system was determined to be 5.8 million in 2015; this was approximately three times higher than it was when the system was implemented in 2000. 2,3 Most of the individuals have specific medical conditions that are associated with pressure injury development; 4 consequently, the number of individuals at risk of developing pressure injuries at home in Japan appears to be increasing. Reportedly, this incidence rate was 13%, 5 which was higher than that in patients admitted to university and general hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…31 Margolis discussed multiple medical conditions in regression analysis as risk factors for PUs in an outpatient setting. 32 These studies highlight distinct systemic factors (aging-related conditions, diseases, and frailty dysfunction) contributing to the development of PU.…”
Section: Systemic Medical Factorsmentioning
confidence: 99%
“…Studies have shown that there are several risk factors that are associated with the development of pressure ulcers (Margolis, Knauss, Bilker, and Baumgarten, 2003). While there is still some lack of clarity relating to the cause and risk factors for pressure ulcers development, most researchers concur that the origin of this problem relates to two categories; intrinsic risk factors and extrinsic risk factors (Cannon and Cannon, 2004;and Magalhdes et al 2007).…”
Section: Causes Of Pressure Ulcersmentioning
confidence: 99%
“…Conditions that have been implicated by multivariate analysis as causes or risk factors for pressure ulcer development include, hypotension, peripheral vascular disease, cerebo-vascular disease, heart failure, diabetes, obstructive pulmonary disease, and stroke (Allman, Goode, Patrick, Burst, and Bartolucci, 1995;Bergstrom and Braden, 1992;Ducker, 2002;Garcia and Thomas, 2006;Margolis, Knauss, Bilker, and Baumgarten, 2003). In a cohort study to evaluate the risk of pressure ulcer development in the presence of certain medical conditions in older ambulatory patients, Margolis, Knauss, Bilker, and Baumgarten (2003) studied 75,168 older individuals from an outpatient record database in the United Kingdom.…”
Section: Physical Factorsmentioning
confidence: 99%
See 1 more Smart Citation